2020
DOI: 10.1111/vsu.13406
|View full text |Cite|
|
Sign up to set email alerts
|

Long‐term survival after treatment of idiopathic lung lobe torsion in 80 cases

Abstract: Objective: To report outcomes of dogs treated for lung lobe torsion (LLT) and to determine prognostic factors for survival.Study design: Retrospective multicenter study from four veterinary teaching hospitals.Animals: Dogs (n = 80) with LLT. Methods: Medical records were reviewed for clinical and histopathological findings. Long-term outcome was assessed with an owner questionnaire. Lung lobe torsion was classified as idiopathic or secondary on the basis of the etiology. Results: The most represented breeds we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 25 publications
2
22
0
Order By: Relevance
“…The preferred surgical approach for lung lobectomy is intercostal thoracotomy due to reduced postoperative morbidity, 18 but median sternotomy was deemed more appropriate to allow better visualisation and to facilitate thorough thoracic exploration in this case. Lung lobectomy is the treatment of choice for LLT in dogs and cats 1,2,10 . Despite past perceptions of high complication rates and mortality associated with this procedure, recent studies have demonstrated excellent survival rate between 92% and 100% 1,2,19 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The preferred surgical approach for lung lobectomy is intercostal thoracotomy due to reduced postoperative morbidity, 18 but median sternotomy was deemed more appropriate to allow better visualisation and to facilitate thorough thoracic exploration in this case. Lung lobectomy is the treatment of choice for LLT in dogs and cats 1,2,10 . Despite past perceptions of high complication rates and mortality associated with this procedure, recent studies have demonstrated excellent survival rate between 92% and 100% 1,2,19 …”
Section: Discussionmentioning
confidence: 99%
“…Lung lobectomy is the treatment of choice for LLT in dogs and cats 1,2,10 . Despite past perceptions of high complication rates and mortality associated with this procedure, recent studies have demonstrated excellent survival rate between 92% and 100% 1,2,19 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…2,3 While the cause of LLT is unknown, increased lobe mobility associated with thorax conformation, increased perilobar space, bronchial cartilage dysplasia and lobar pathology have been linked to its occurrence in veterinary species. 1,46…”
Section: Introductionmentioning
confidence: 99%